Selected papers from the 11th international symposium on electromagnetics fields in electrical engineering ISEF 2003 - Wiak, S. (International journal for computation and mathematics in electrical and electronic engineering., 2004)
This paper presents a curvilinearlyestablished finite-difference time-domain methodology for the enhanced 3D analysis of electromagnetic and acoustic propagation in generalised electromagnetic compatibility devices, junctions or bent ducts. Based on an exact multimodal decomposition and a higherorder differencing topology, the new technique successfully treats complex systems of varying cross-section and guarantees the consistent evaluation of their scattering parameters or resonance frequencies. To subdue the non-separable modes at the structures' interfaces, a convergent grid approach is dev.